"Born with the taste for science and the arts": The science and the aesthetics of Balthazar‐Georges Sage's mineralogy collections, 1783–18251. (28th August 2019) - Napolitani, Maddalena
Abstract: Balthazar‐Georges Sage (1740–1824), a chemist, mineralogist, and the founder of the École Royale des Mines (1783), owned two mineral collections: a mineralogy collection used for his research and teaching, which later became the property of the École Royale itself; and a private cabinet of objets d'art, consisting largely of artistically worked mineral objects. Although created for different purposes, Sage valued both for their utility and their aesthetics. This paper explores the dual character of the collections by presenting Sage as a man of science and an art lover. It argues that his lifelong concern with aesthetics was the underlying link between the two collections, his teaching practices, and his aim in founding of the École Royale des Mines to improve France's mining industry. Through aesthetics, Sage sought to build a coherent whole, which he referred to as a "national monument, " consisting of the collections, the school, and his work as a teacher and a mineralogist. In the years leading up to the French Revolution, the collections—a central part within this coherent whole—were the key element in establishing the social identity of the new institution as well as that of Sage himself. In the context of political upheaval, the social, economic, and aesthetic value of the collections became tied to the political aims of the republic, in particular, its interest in building the new nation through its heritage as conserved in its national monuments: the new republican museums. Sage used the term museum to define both collections: this analysis of their relationship and the different functions he attributed to them reveals how profoundly collecting practices were changing in revolutionary and post‐revolutionary France.